Análisis financiero a la empresa distribuciones representaciones y exportaciones Direxloja S.A., de la ciudad de Loja periodo 2013- 2014 - Buele Ojeda, Janina Soledad (2016)
This thesis called FINANCIAL ANALYSIS TO THE COMPANY DISTRIBUTIONS REPRESENTATIONS AND EXPORTS DIREXLOJA SA, CITY OF LOJA PERIOD 2013- 2014, was carried out based on the general and specific objectives set out in the project to meet one of the prior to obtain the Engineering degree in Accounting and Auditing CPA, which was developed based on the General Standards Graduation Career Accounting and Auditing of the Legal Department, Social and Management of the National University of Loja requirements. The thesis is to assess the financial position of the company applying a Financial Analysis it containing the application of a horizontal analysis it allows us to determine the absolute and relative change that has suffered each item or account states financial of a period to the other, ie allowed to determine the behavior of the company if this was good, average or bad, vertical analysis it is of great importance in establishing the distribution of assets also applies in an equitable manner and according to the financial needs of the company and also reasons or financial indicators which served to identify weaknesses of the company or abnormalities that may affect the company these indicators consist with graphs and interpretations were applied respective for greater understanding, in the financial analis are also included according to the objectives proposed implementing financial statements projected them that are very useful because they provide updated information to make decisions related to their future operations information and finally performed a proposal to improve it which is part of the training of company personnel for both the administrative staff and the plant in the training of addressing issues such as customer service among others the same that will be very useful for the company and the community in general. Traductor de Google para empresas:Google Translator ToolkitTraductor de sitios webGlobal Market Finder